2018
DOI: 10.3390/s18082696
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Computational and Experimental Detection of Adenosine Using Ultrasensitive Surface-Enhanced Raman Spectroscopy

Abstract: To better understand detection and monitoring of the important neurotransmitter adenosine at physiological levels, this study combines quantum chemical density functional modeling and ultrasensitive surface-enhanced Raman spectroscopic (SERS) measurements. Combined simulation results and experimental data for an analyte concentration of about 10−11 molar indicate the presence of all known molecular forms resulting from adenosine’s complex redox-reaction. Detailed analysis presented here, besides assessing pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For this reason, we can observe the band at ~1615 cm −1 , while the signal at 1560 cm −1 remains embedded in overlap with other vibrational signals from purines. In further support of the hypothesis of dATP oxidation, a recent study by Sundin et al [ 181 ] compared computed and experimental Raman spectra of adenosine before and after successive oxidation steps. These researchers reported that the fully oxidized adenosine form contributes mostly to the enhancement of the signal at around 1600 cm −1 , with no significant changes in the vibrational signatures of the furanose ring.…”
Section: Applications Of In Situ Raman Spectroscopy To Microbiologymentioning
confidence: 98%
“…For this reason, we can observe the band at ~1615 cm −1 , while the signal at 1560 cm −1 remains embedded in overlap with other vibrational signals from purines. In further support of the hypothesis of dATP oxidation, a recent study by Sundin et al [ 181 ] compared computed and experimental Raman spectra of adenosine before and after successive oxidation steps. These researchers reported that the fully oxidized adenosine form contributes mostly to the enhancement of the signal at around 1600 cm −1 , with no significant changes in the vibrational signatures of the furanose ring.…”
Section: Applications Of In Situ Raman Spectroscopy To Microbiologymentioning
confidence: 98%
“…The agreement between calculated vibrational bands and experimental SERS bands is similar to that seen previously in the literature for other molecules. 49–52 According to the theoretical calculations (Table III) and the Ag colloid paste blank spectrum (Fig. S5), the starred peak at 793.9 cm –1 is attributed to the silver colloid paste.…”
Section: Resultsmentioning
confidence: 96%
“…48 The calculated vibrational bands and experimental SERS spectra agree relatively well with some discrepancies, as has been seen previously in the literature for other molecules. 49–52 In addition, when the molecule is bonded to the metal, the peak intensity can change based on the orientation of the molecule. The most intense peaks in all the experimental spectra are in-plane vibrations suggesting that the molecules are oriented perpendicular to the nanoparticle surface.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated Raman spectra were in good agreement with the experimental results (Figure ), which is important to validate that our DFT calculations were implemented appropriately. The calculated Raman spectra of adenine and adenosine also agreed well with previous reports, which also verifies that our DFT calculations were performed correctly. , Note that one cannot expect the exact same Raman spectra for both calculation and experiment due to variations in the conditions under which the respective spectra are acquired. For example, a single isolated molecule is considered in DFT, whereas aggregated molecules in the powder form are analyzed experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…We then compared the Raman spectra of COA-Cl with those of adenine and adenosine. Adenine and adenosine have been extensively studied by Raman spectroscopy and are expected to exhibit similar Raman spectroscopic characteristics as their molecular structures are similar to that of COA-Cl. Figure shows the Raman spectra of adenine and adenosine.…”
Section: Resultsmentioning
confidence: 99%